2017
DOI: 10.1002/14651858.cd005661.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Closure methods for laparotomy incisions for preventing incisional hernias and other wound complications

Abstract: Closure methods for laparotomy incisions for preventing incisional hernias and other wound complications (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 96 publications
4
82
1
7
Order By: Relevance
“…Average time for mass closure (20 minutes) was considerably less as compared to layered closure (35 min). 17 Similar conclusions were also reported by the authors such as Chalya et al and Patel et al 18,19 Finally the analysis of complications in studied patients showed that out of 30 patients in group A (layered sutures) 11 (36.67%) patients developed complications and most common complication was found to be wound infection and wound gaping which was seen in 3 (10%) patients each. In group B hematoma, surgical site infection and incision hernia was seen in 1 patient (3.33%) each.…”
Section: Discussionsupporting
confidence: 79%
“…Average time for mass closure (20 minutes) was considerably less as compared to layered closure (35 min). 17 Similar conclusions were also reported by the authors such as Chalya et al and Patel et al 18,19 Finally the analysis of complications in studied patients showed that out of 30 patients in group A (layered sutures) 11 (36.67%) patients developed complications and most common complication was found to be wound infection and wound gaping which was seen in 3 (10%) patients each. In group B hematoma, surgical site infection and incision hernia was seen in 1 patient (3.33%) each.…”
Section: Discussionsupporting
confidence: 79%
“…Surgical techniques may be able to reduce the SSI rate, and ideal approaches have long been examined, including antimicrobial suture and methods of abdominal closure . However, these previous reports have focused on open colorectal surgery, and there are few reports of risk factors for incisional SSI with laparoscopic colorectal surgery (Lap CR).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rise of laparoscopic surgery, open abdominal surgery by a midline laparotomy is still the most performed approach in abdominal surgery today (35). Regardless of improvements in the surgical techniques of abdominal wall closure, IH incidence remain high and cause substantial morbidity and costs (24).…”
Section: Discussionmentioning
confidence: 99%